UNESCO and its role in protecting cultural property during armed conflicts (the war on Iraq and Syria) is an example (Latakia University Journal - Economic and Legal Sciences Series, 2024)
Wars and their effects didn’t confine on soldiers and fighting fields but also extended to civilians and cities with their culture properties which their age thousands of years. There are many reasons for targeting these properties from attempts to erase the history of peoples and pressure on conflicts parties to considering that kind of material and moral victory, with increasing in culture properties targeting during the armed conflicts which called on the international community to find a mechanism its mission is saving these properties, so the United Nations Educational, Scientific and Culture Organization(UNESCO) has appeared and worked to put the international conventions and to provide the necessary means to save culture properties in all circumstances including  armed conflicts and it faced great difficulties to achieve that.